Integrating urban energy systems into a mixed-use urban redevelopment - Miranda, Mikaela Jlouis M.; Balane, Ronald S. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
The negative effects of climate change are greatly intensified by the growth of urbanization in cities. As cities continue to utilize the world’s resource, they are majorly responsible for the greenhouse gas emission contribution to the atmosphere. Urban development costs a lot of energy to continue developing whilst generating a waste of unused energy at the same time.
Moreover, the drive of urbanization continues to worsen the socio-economic divide, bringing about an increase of poverty and poor living conditions. The impoverished communities significantly face vulnerability towards their current living situation and environment. Vitas Katuparan is a National Housing Authority Project in Tondo, Manila currently facing issuances of demolition and reconstruction. Both its structural and environmental fragility creates a hazardous state of living for the existing residing community.
The design project aims to create a redevelopment that would cater to the needs of the community by providing spaces for socio-economic opportunities; whilst tackling environmental issues by applying energy systems and strategies to reinforce resilience within the development. This will be done by combining residential, commercial, and industrial spaces; as well as, incorporating a façade sun shading mechanism, rainwater harvesting system and a green roof. Through a mixed-use approach and energy system integration, there is a high potential to redevelop and rehabilitate the existing site to create a safer, resilient and energy efficient place for the community.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Mixed-use buildings -- Tondo (Manila); Sustainable buildings -- Tondo (Manila)